WACANA TUJAQI PADA PROSESI ADAT PERKAWINAN MASYARAKAT SUWAWA PROVINSI GORONTALO - Fatmah AR. Umar (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
The  purpose  of  this  researcth  are  explain  scheme,  actor, setting, and theme of tujaqi discourse in procession of married culture in Suwawa society  Gorontalo  Province,  in  the  statge  of  motolobalango,   momanato,  and moponika. This Researceh is using qualitative approach. The result of this research are (1) scheme of tujaqi discourse in procession of marrid culture Suwawa sosioty Gorontalo Province is using stef forward (benning, middle, and end), (2) actor that involved in tujaqi discourse in procession of married culture Suwawa sosioty Gorontalo Provinece consist of many components from senior official until masses including children, (3) setting of tujaqi discourse is patterning setting and spontane ous setting, and (general theme of tujaqi discourse in procession of married culture Suwawa sosioty Gorontalo Province is struggle, making sacrifice and confession